Two Guanylylcyclases Regulate the Muscarinic Activation of Airway Smooth Muscle - Alfonzo, Marcelo J.; Placeres-Uray, Fabiola; Hassan-Soto, Walid; Borges, Adolfo; Alfonzo, Ramona González de; Becemberg, Itala Lippo de (IntechOpen, 2012)
None